Development of Problem-Based Blended Learning (PBBL) Assisted by Articulate Storyline to Optimize Critical Thinking Skills - Mutia, Tuti; Rosida, Fatiya; Wahyuningtyas, Neni; Rofiki , Imam (Lectura : Jurnal Pendidikan, 2025)
The development of technology in education becomes more advanced by utilizing learning models assisted by digital media. These innovations allow for more flexible and interactive teaching methods, increasing student engagement and understanding. Technology based learning enables broader access to information and allows students to learn independently. By using digital media, students understand difficult concepts and interact directly with the material. This study aims to develop Problem-Based Blended Learning (PBBL) assisted by articulate storylines. The method used was designed using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) research model. The analysis in this study employed qualitative descriptive and quantitative descriptive analysis. The research instrument was in the form of a validation questionnaire for learning experts and media validation. The results of the study showed that learning experts obtained a score of 88% (very worth it) and media experts obtained a score of 80% (very worth it). The results of the small group questionnaire, the product receives score of 95 out of the ideal score of 100. This indicates that the product is highly feasible and can be implemented without revision. So, it can be concluded that PBBL assisted by articulate storylines is an effective learning approach. PBBL based on Articulate Storyline has great potential to be applied in the curriculum as a learning medium that adapts to various subjects. This technology integration not only answers the challenges of problem-based learning but also enriches students' experiences, increases their engagement, and supports more student-centered learning. Additionally, it encourages collaborative learning and critical thinking.